Analisis Efisiensi dan Efektivitas Pengelolaan Dana Desa pada Kantor Desa Kalebarembeng Kecamatan Bontonompo Kabupaten Gowa - Betaria Nur; Nurmega Nurmega; Elisabeth Ambalele (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This research aims to analyze the efficiency and effectiveness of budget management in Kalebarembeng village, Bontonompo District, Gowa Regency. The type of research used in this research is descriptive quantitative with the formula: Efficiency Ratio and Effectiveness Ratio. The data processed is primary data in the form of a report on the realization of the village income and expenditure budget using Kalebarembeng village government funding sources for the 2019-2023 period. The results of the research show that the level of efficiency in managing the Kalembarembeng village budget is still in the less efficient category, but the level of effectiveness is in the effective category. This situation means that the goals of the Kalebarembeng village government can be achieved but at very high costs.